2020
DOI: 10.1038/s41598-020-69143-3
|View full text |Cite
|
Sign up to set email alerts
|

Control of the galactose-to-glucose consumption ratio in co-fermentation using engineered Escherichia coli strains

Abstract: Marine biomasses capable of fixing carbon dioxide have attracted attention as an alternative to fossil resources for fuel and chemical production. Although a simple co-fermentation of fermentable sugars, such as glucose and galactose, has been reported from marine biomass, no previous report has discussed the fine-control of the galactose-to-glucose consumption ratio in this context. Here, we sought to finely control the galactose-to-glucose consumption ratio in the co-fermentation of these sugars using engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In a recent report, it was reported that the wild-type E. coli W3110 cells first consumed glucose rapidly with a rate of 1.37 g/gDCW/h, followed by galactose consumption with a rate of 0.04 g/gDCW/h in both sugars co-fermentation [20]. This indicates that galactose consumption was strictly inhibited by the CCR mechanism in the W3110 strain (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…In a recent report, it was reported that the wild-type E. coli W3110 cells first consumed glucose rapidly with a rate of 1.37 g/gDCW/h, followed by galactose consumption with a rate of 0.04 g/gDCW/h in both sugars co-fermentation [20]. This indicates that galactose consumption was strictly inhibited by the CCR mechanism in the W3110 strain (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…1). In the previous report, under the glucose and galactose co-fermentation (each 4 g/L), the E. coli GR2 cells showed a similar specific glucose consumption rate of the W3110 strain [20]. However, in the same co-fermentation, the GR2 strain achieved a 3.38 times increase in specific galactose consumption rate [20].…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations